Tarîqah Al-Tikrar Fî Hifzhi Al-Qur’an (Dirâsah al-Hâlât Bi Ma’had Al-Muqaddasah, Ponorogo) - Ilham Habibullah; Raihan Arafah (Studia Quranika, 2020)
The Method selection is a very pivotal factor in memorizing Qur'an. The method that is often used is ‘Tikrar’ or the method of repetition, This method that has long been applied in the time of the prophet Muhammad SAW. One of boarding school of the “tahfidz” that used this method is “Pondok Pesantren Al-Muqaddasah” to help students memorize Qur'an. The application of repetiton methods in memorizing the Qur’an takes a long time. However in applying the repetition method “Al-Muqaddasah”is able to manage it as well so that it can run optimally. Departing from the background above, the writer tries to uncover and to examine about how the application of repetition method and tahfidz in “Pondok Pesantren Al-Muqaddasah”. The writer uses the method of data collection that is done through observation, interviews, and documentation. While to analyz the data ontained from the results of the study, the writer used existing data to describe reality in accordance with the actual event. The results achieved by the research using the method discussed “Pondok Pesantren Al-Muqaddasah” add new memorization and repeat memorization beforehand so that the memorization remains embedded in memory. The inhibiting factor in repetition method process is the presence of laziness or the persence of environmental factors, forgeting the previos verse. The strategy to support this methode is to foster self-motivation to always memorize the Qur’an with tadabbur verses where students must know the causes and consequenses of memorizing the Qur’an.